Effects of Attention Direction and Perceptual Distraction Within Visual Working Memory - Zheng, Weixi; Jia, Liping; Sun, Nana; Liu, Yu; Geng, Jiayang; Zhang, Dexiang (Frontiers in Psychology, 2022)
Although substantial evidence demonstrates that directing attention to specific items is important for improving the performance of visual working memory (VWM), it is still not clear whether the attended items were better protected. The present study, thus, adopted a pre-cueing paradigm to examine the effect of attention direction and perceptual distractor on VWM. The results showed that a valid visual cue improved the individuals’ VWM performances and reduced their reaction time compared to the invalid and neutral cues. However, the VWM performances in the valid and neutral cue conditions were more disrupted by a post-stimuli distractor compared to the invalid cue condition. The findings suggest that although directing attention can improve the VWM performance, it is not efficient in protecting information from being distracted.